PENERAPAN MODEL PROBLEM BASED LEARNING DAN MODEL PEMBELAJARAN LANGSUNG PADA PEMBELAJARAN MATEMATIKA OPERASI MATRIKS DI SMK N 1 TOULUAAN - Panekenan, Calvin; Pulukadang, Rosiah J.; Pesik, Anneke (SOSCIED, 2024)
This study examines the application of two different learning models in learning matrix operation mathematics at SMK N 1 Touluaan. This research used experimental method with pretest-posttest experiment group design, involving two randomly selected classes with the number of samples of each class of 20 students and the experimental class applied Problem-Based Learning and the control class applied direct learning. The results showed that there was a significant difference between the learning outcomes of students taught using the Problem-Based Learning model and students taught using the direct learning model. In this study using the t-test to test the data, with the results of the value of t_hitung = 3.239041637> t_tabel = 1.68595 with a real level Î± = 0.05 this means reject H_0 and accept H_1. The Problem-Based Learning model is proven effective in improving student learning outcomes on matrix operation material.